2022
DOI: 10.1186/s13014-022-02105-3
|View full text |Cite
|
Sign up to set email alerts
|

Organs-at-risk dose constraints in head and neck intensity-modulated radiation therapy using a dataset from a multi-institutional clinical trial (JCOG1015A1)

Abstract: Background JCOG1015A1 is an ancillary research study to determine the organ-specific dose constraints in head and neck carcinoma treated with intensity-modulated radiation therapy (IMRT) using data from JCOG1015. Methods Individual patient data and dose-volume histograms of organs at risk (OAR) were collected from 74 patients with nasopharyngeal carcinoma treated with IMRT who enrolled in JCOG1015. The incidence of late toxicities was evaluated us… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 40 publications
1
6
0
Order By: Relevance
“…Our results showed that the Dmean and V40 of the thyroid and the Dmean of the larynx in group 1 were significantly lower than those in group 2. Although all these values were lower than the cutoff value suggested by most studies, 18,20,21 considering the low regional recurrence rates in the two groups, the smaller target volume strategy was the optimal choice.…”
Section: Discussionmentioning
confidence: 63%
“…Our results showed that the Dmean and V40 of the thyroid and the Dmean of the larynx in group 1 were significantly lower than those in group 2. Although all these values were lower than the cutoff value suggested by most studies, 18,20,21 considering the low regional recurrence rates in the two groups, the smaller target volume strategy was the optimal choice.…”
Section: Discussionmentioning
confidence: 63%
“…The article comes to the conclusion that SC-VMAT with three full arcs was inferior in dosimetry to DC-VMAT with a single arc (15) . Colli-VMAT plans with smaller angular sections (16) have comparable target coverage and spare healthy tissues in comparison to Std-VMAT https://www.indjst.org/ plans (17) , according to analysis by Beom Seok Ahn et al In the same (16) , a precise substantial decrease in total MUs was also noted.…”
Section: Resultsmentioning
confidence: 99%
“…Swallowing difficulties are a prevalent side effect of radiotherapy (RT) treatments for head and neck cancers (1)(2)(3)(4)(5). RT involves targeting cancers with a three-dimensional (3D) radiation dose.…”
Section: Introductionmentioning
confidence: 99%